Rheological Response Under Nonisothermal Stretching For Immiscible Blends Of Isotactic Polypropylene And Acrylate Polymer - Seemork, Jiraporn; Sako, Takumi; Md Ali, Mohd Amran; Yamaguchi, Masayuki (Society Of Rheology, 2017)
The addition of acrylate polymers with low molecular weight, such as poly(isobutyl methacrylate) (PIBM) and poly(methyl methacrylate) (PMMA), effectively enhances the force required to stretch a molten polypropylene (PP) at the nonisothermal condition without the enhancement of shear viscosity in the molten state. The mechanism of this phenomenon is found to be attributed to prompt solidification of PIBM and PMMA droplets, which deform greatly to the flow direction in the die land and near the die exit during the extrusion and stretching processes. After the die exit, the deformed droplets show the glassification prior to the crystallization of PP matrix because of the rapid cooling at stretching. Consequently, they behave like rigid fibers in a molten PP, which provide the excess stress by large shear deformation of the matrix between the dispersed glassy fibers during stretching.